The boy in the plastic bubble - Kleiser, Randal; Travolta, John, 1954-; O'Connor, Glynnis; Reed, Robert, 1932-1992; Spelling-Goldberg Productions; Cinetel Films ([Los Angeles, CA] : Spelling-Golberg Productions, 1976)
Based on a true story, Tod Lubitch is born with a deficient immune system. As such, he must spend the rest of his life in a completely sterile environment. His room is completely hermetically sealed against bacteria and virus, his food is specially prepared, and his only human contact comes in the form of gloved hands. The movie follows his life into a teenager. --
Originally broadcast in ABC.
John Travolta, Glynnis O'Connor, Robert Reed, Diana Hyland, Karen Morrow, Howard Platt, Buzz Aldrin, Ralph Bellamy.
Produced by Joel Thurm and Cindy Dunne; screenwriter, Douglas Day Stewart.
Cinematographer, Archie Dalzell; editor, John F. McSweeney; music, Mark Snow.
In English or Spanish.
Winner of 1 Primetime Emmy: Outstanding Performance by a Supporting Actress in a Comedy or Drama Special (Diana Hyland)
Keywords: Vetter, David, -- 1971-1984 -- Drama; Immunologic diseases -- Drama; Teenage boys -- Drama; Fiction films; Feature films; Independent films; Made-for-TV movies; Biographical films; Internet videos; Streaming video